2019
DOI: 10.1175/jas-d-18-0297.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Divergent Circulation for Large-Scale Eddy Momentum Transport in the Tropics. Part I: Observations

Abstract: This work investigates the role played by the divergent circulation for meridional eddy momentum transport in the tropical atmosphere. It is shown that the eddy momentum flux in the deep tropics arises primarily from correlations between the divergent eddy meridional velocity and the rotational eddy zonal velocity. Consistent with previous studies, this transport is dominated by the stationary wave component, associated with correlations between the zonal structure of the Hadley cell (zonal anomalies in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…While we focus here more on the changes in the midlatitudes, it is worth pointing out that there are significant changes in upper‐level wind speed in the tropics. These wind speed anomalies are similar to those discussed in Zurita‐Gotor (2019), who found that the large‐scale eddy momentum transport in the tropics is associated with the correlation between the divergent meridional velocity and the non‐divergent zonal velocity. They also pointed out that the Hadley circulation plays the dominant role in the tropical momentum transport.…”
Section: Mjo and The Subtropical Jetsupporting
confidence: 88%
“…While we focus here more on the changes in the midlatitudes, it is worth pointing out that there are significant changes in upper‐level wind speed in the tropics. These wind speed anomalies are similar to those discussed in Zurita‐Gotor (2019), who found that the large‐scale eddy momentum transport in the tropics is associated with the correlation between the divergent meridional velocity and the non‐divergent zonal velocity. They also pointed out that the Hadley circulation plays the dominant role in the tropical momentum transport.…”
Section: Mjo and The Subtropical Jetsupporting
confidence: 88%
“…Consistent with previous work(Zurita-Gotor and Held 2018;Zurita-Gotor 2019), the divergent component (in particular the term) is responsible for the equatorial acceleration (Fig.3, top) while the rotational eddy momentum fluxes only decelerate the tropics. To capture the full impact of the latter, we show this term meridionally integrated over the tropics (| | ≤ 20, Fig.…”
supporting
confidence: 90%
“…where overbars and primes denote zonal averages and deviations therefrom and the and suscripts denote the rotational and divergent velocity contributions to the horizontal velocity ( , ), is vertical vorticity and horizontal divergence. We used a Cartesian expression above for simplicity (see Zurita-Gotor (2019) for the full spherical expressions including cosine factors). The cospectra show that these two eddy contributions to the equatorial momentum balance are due to different waves.…”
Section: Analysis Of Williams' Resultsmentioning
confidence: 99%
“…However, Hartley and Black (1995) found that in their climate model the momentum fluxes on the equator that are equatorward in the Northern Hemisphere winter were associated with convective outflow rather than Rossby wave propagation and tilted troughs. Also, Zurita-Gotor (2019) found that the near equatorial momentum transfers were dominated by the correlation of the divergent meridional wind and the rotational zonal wind.…”
Section: Introductionmentioning
confidence: 98%